Real-life resilience in international water utilities - Giffoni, Eduarda (Cranfield University, 2022)
Resilience is a highly aspired capability for the water sector. Whilst the concept has been vastly utilised in technocentric and engineering objectives, few studies have investigated the human dimensions of resilience in the context of international water utilities. Specifically, little is known about how the organisational environment, organisational culture and engagement with water customers may contribute to the resilience of the water sector and the challenges and opportunities of building resilience capabilities in these domains. As the central context for this research, water utilities provide critical socio-economic utility to society. Disruptions felt by water utilities can negatively impact multiple communities, regional prosperity, and national security. However, water utilities monopoly nature may insulate them from the new and evolving demands derived from the free market, thus delaying the organic development of adaptive and agile capabilities. In addition, given that the infrastructure of water utilities tends to be ‘locked-in’ to a fail- safe stance, this bleeds through the organisation’s norms and beliefs, thus further perpetuating previous paths and hindering experimentation and transformative change. This is problematic because water utilities are more sensitive to local shocks and stresses as they are bound to local catchments and providing services to local communities, as opposed to energy utilities that may source energy from a wide range of geographical locations. All these factors make water utilities an interesting population of research from the lenses of Organisational Resilience. Therefore, this thesis aims to understand the current stance and context within international water utilities in relation adaptability and Organisational Resilience – ii spanning the organisational environment, culture, and interactions with customers. This work seeks to critically evaluate how the organisational and human capabilities may be shaped to enhance water sector resilience and the challenges and opportunities of doing so. Through semi-structured interviews and an iterative survey with international water utilities this qualitative research captures perceptions from water managers on embedding Organisational Resilience properties. This research provides several contributions to the current body of knowledge. Primarily, the findings empirically identified novel challenges utilities face - spanning the cognitive frame, behaviour of individuals, and the context of the organisational environment - which flagged some key developmental areas to establish an organisational setting conducive of resilience. For instance, chapter 2 delves deep into the organisational environment in water utilities. and identifies a need to broaden the cognitive frame of utilities to account for flexible concepts for enhanced sense-making and proposes novel categories of organisational silos and a set of cultural attributes that contribute to organisational resilience. Moreover, chapter 3 explores the contextual property of organisational resilience, based on external relationships, to examine how customers may influence the resilience of water utilities. Although it was recognised a role of customers as passive beneficiaries of resilience, positive roles were also identified, such as: facilitators of more targeted initiatives, contributors to higher tolerance levels and positive behaviour-change, and resilience advocates. An additional contribution of this research is the creation of a framework of an organisational culture of organisational resilience for the water sector in chapter 4. A iii novel set of cultural attributes that were validated as conducive to the Organisational Resilience of water utilities were appraised from relevant literature. Derived based on the perspectives of utility managers, the set of cultural attributes clarifies Organisational Resilience beliefs and values that should shape individuals’ behaviour and the organisational environment. Thematic analysis identified an over-emphasis on standards and procedures that may hinder positive changes towards a culture of organisational resilience. In addition, addressing organisational barriers perceived as a pre-requisite to cultural changes, which may lead to inaction. However, the water sector’s impetus for talent recruitment and staff retention translated as an appetite to foment deeper relational ties with personnel. Finally, this study highlights a real need for transforming the beliefs, values, and behaviour in water utilities to implement and sustain efforts in the human and organisational dimensions that are conducive of Organisational Resilience. Such resilience transformation will entail efforts in the cognitive, behavioural, and contextual aspects within utilities to address current challenges and leverage identified opportunities.
Jude, Simon - Associate Supervisor
Keywords: Organisational resilience; organisational culture; water customers; human resilience; international water utilities; water resilience